Overexpression of ABCB1 Associated With the Resistance to the KRAS-G12C Specific Inhibitor ARS-1620 in Cancer Cells - Dong, Xing-Duo; Zhang, Meng; Cai, Chao-Yun; Teng, Qiu-Xu; Wang, Jing-Quan; Fu, Yi-Ge; Cui, Qingbin; Patel, Ketankumar; Wang, Dong-Tao; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2022)
The KRAS-G12C inhibitor ARS-1620, is a novel specific covalent inhibitor of KRAS-G12C, possessing a strong targeting inhibitory effect on KRAS-G12C mutant tumors. Overexpression of ATP-binding cassette super-family B member 1 (ABCB1/P-gp) is one of the pivotal factors contributing to multidrug resistance (MDR), and its association with KRAS mutations has been extensively studied. However, the investigations about the connection between the inhibitors of mutant KRAS and the level of ABC transporters are still missing. In this study, we investigated the potential drug resistance mechanism of ARS-1620 associated with ABCB1. The desensitization effect of ARS-1620 was remarkably intensified in both drug-induced ABCB1-overexpressing cancer cells and ABCB1-transfected cells as confirmed by cell viability assay results. This desensitization of ARS-1620 could be completely reversed when co-treated with an ABCB1 reversal agent. In mechanism-based studies, [3H] -paclitaxel accumulation assay revealed that ARS-1620 could be competitively pumped out by ABCB1. Additionally, it was found that ARS-1620 remarkably stimulated ATPase activity of ABCB1, and the HPLC drug accumulation assay displayed that ARS-1620 was actively transported out of ABCB1-overexpressing cancer cells. ARS-1620 acquired a high docking score in computer molecular docking analysis, implying ARS-1620 could intensely interact with ABCB1 transporters. Taken all together, these data indicated that ARS-1620 is a substrate for ABCB1, and the potential influence of ARS-1620-related cancer therapy on ABCB1-overexpressing cancer cells should be considered in future clinical applications.